Integrated analyses of single-cell transcriptomics identify metastasis-associated myeloid subpopulations in breast cancer lung metastasis - Huang, Zhen; Bu, Dawei; Yang, Nan; Huang, Wenwen; Zhang, Liyin; Li, Xiaoxue; Ding, Bi-Sen (Frontiers in Immunology, 2023)
Lung metastasis of breast cancer is closely associated with patient morbidity and mortality, which correlates with myeloid cells in the lung microenvironment. However, the heterogeneity and specificity of metastasis-associated myeloid cells have not been fully established in lung metastasis. Here, by integrating and analyzing single-cell transcriptomics, we found that myeloid subpopulations (Tppp3+ monocytes, Isg15+ macrophages, Ifit3+ neutrophils, and Il12b+ DCs) play critical roles in the formation and development of the metastatic niche. Gene enrichment analyses indicate that several tumor-promoting pathways should be responsible for the process, including angiogenesis (Anxa1 and Anxa2 by Tppp3+ monocytes), immunosuppression (Isg15 and Cxcl10 by Isg15+ macrophages; Il12b and Ccl22 by Il12b+ DCs), and tumor growth and metastasis (Isg15 and Isg20 by Ifit3+ neutrophils). Furthermore, we have validated these subpopulations in lung microenvironment of MMTV-PyVT transgenic mice and verified their association with poor progression of human breast cancer. Also, our results elucidated a crosstalk network among four myeloid subpopulations by cell-cell communication analysis. This study, therefore, highlights the crucial role of myeloid cells in lung metastasis and provides insights into underlying molecular mechanisms, which pave the way for therapeutic interventions in breast cancer metastasis to lung.